Enhancing Mathematical Critical Thinking through Problem-Based Learning: A Case Study at SMP Pangeran Antasari - Rizky Anta; Weni Widya Asriati; Nur Tri Julia (Information Technology and Science (ITScience), 2025)
This study aims to analyze the effect of Problem-Based Learning (PBL) on students’ mathematical critical thinking skills in solving Systems of Linear Equations in Two Variables (SPLDV). A qualitative descriptive approach was employed with 30 grade VIII students at SMP Pangeran Antasari as research subjects. Data were collected through tests, observations, interviews, and documentation, with instrument reliability confirmed using Cronbach’s Alpha (0.627). The findings show that 80% of students successfully identified problems, 75% provided logical reasoning, 70% connected mathematical concepts with real-life contexts, 85% applied appropriate solution strategies, and 78% drew valid conclusions. Nevertheless, around 20% of students demonstrated only moderate performance, and 10% showed significant difficulties in reasoning and inference. These results confirm that PBL enhances student engagement, collaborative learning, and higher-order thinking, while also highlighting the need for scaffolding to strengthen reasoning and inferencing skills. This research contributes empirical evidence supporting the application of PBL in mathematics classrooms and reinforces its alignment with constructivist learning theories and 21st-century skill development.